Isolation of marine bacteria with potential for polyhydroxyalkanoate degradation and optimization for enzyme production - Antika Boondaeng; Chanaporn Trakunjae; Pilanee Vaithanomsat; Nanthavut Niyomvong (Scientific Reports)
Abstract Plastic materials are widely used because of their strength, light weight, durability, and environmental resistance. However, their decomposition rates are significantly slower than their typical lifespans. The rapid and continuous increase in plastic consumption has caused severe environmental impacts due to the accumulation of plastic waste. We identified potential polyhydroxyalkanoate (PHA)-degrading bacteria from marine environments capable of producing extracellular PHA depolymerases crucial for biodegrading PHAs. Marine debris was collected to screen poly [(R)-3-hydroxybutyric acid] (P(3HB))-degrading bacteria. Six isolates showed the ability to produce clear zones surrounding their colonies by degrading the bioplastic P(3HB). The isolate SS1-2, exhibiting the greatest degradation index of 1.44, was chosen for optimization through the statistical technique. The results indicated that NH4Cl was the best nitrogen source for enzyme production, and the response surface methodology (RSM) suggested that the greatest P(3HB) depolymerase production could be achieved when the concentrations of substrate loading and NH4Cl both set at 0.5%. Analysis of the 16S rRNA sequence of isolate SS1-2 revealed similarity to Pseudooceanicola antarcticus CGMCC 1.12662 (97.81% similarity). The findings of this study indicate the potential for further exploitation of this depolymerase in enzyme kinetics studies and its application in PHA degradation experiments.